2019
DOI: 10.1016/j.eurpsy.2019.04.003
|View full text |Cite
|
Sign up to set email alerts
|

The treatment gap for mental disorders and associated factors in the Czech Republic

Abstract: Objectives:To assess the extent of the treatment gap for mental disorders in the Czech Republic, determine factors associated with the utilization of mental health services and explore what influences willingness to seek mental health care.Methods:Data from the CZEch Mental health Study, a nationally representative study of community-dwelling adults in the Czech Republic were used. The Mini International Neuropsychiatric Interview assessed the presence of mental disorders. 659 participants with current affecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 34 publications
4
27
0
Order By: Relevance
“…In another study examining a UK schooling reform in 1972, which raised the minimum school leaving age from 15 to 16 years old, Avendano et al found that although the reform increased EA, it did not decrease depression in adulthood [34]. Our study is unique due to the following reasons: First, it includes by far the largest sample; second, its results can be generalized to a wide geographical area including countries from CEE that have been underrepresented in previous research on mental health [35][36][37][38]; third, we were able to adjust for a wealth of sociodemographic and health-related characteristics.…”
Section: Discussionmentioning
confidence: 93%
“…In another study examining a UK schooling reform in 1972, which raised the minimum school leaving age from 15 to 16 years old, Avendano et al found that although the reform increased EA, it did not decrease depression in adulthood [34]. Our study is unique due to the following reasons: First, it includes by far the largest sample; second, its results can be generalized to a wide geographical area including countries from CEE that have been underrepresented in previous research on mental health [35][36][37][38]; third, we were able to adjust for a wealth of sociodemographic and health-related characteristics.…”
Section: Discussionmentioning
confidence: 93%
“…sectional surveys indicate even a higher rate of alcohol dependency (4). The accessibility of treatment (5) and alcohol associated disability (4) represent related sensitive substantive issues.…”
Section: S30mentioning
confidence: 99%
“…Depression occurs almost twice as frequently in women than in men, affects to a larger extent socioeconomically disadvantaged individuals and is in particular common in Central and Eastern Europe. [1][2][3][4][5] This region has undergone profound structural changes that were initiated by the fall of communistic regimes in 1989, when the countries have transformed their economies from closed and centrally planned toward open and market oriented. 6 Despite major improvements in health and life expectancy of the population after the revolution, 7-9 mental health of several sub-groups of the population may be now threatened.…”
Section: Introductionmentioning
confidence: 99%